Organizational Culture Transformation to Mitigate Human Resource Turnover: A Strategic Change Management Approach in Islamic Private Schools in Bekasi - Milenia An Nisa; Selvia Indrayani; Ihsan Permadi (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze change management strategies in addressing the high intensity of human resource turnover and resistance to digitalization in Islamic faith-based private schools in Bekasi. Using a qualitative approach, the study identifies the root causes as rigid paternalistic culture and bureaucratic inefficiencies. The intervention strategies are designed using Kotter eight-step change model integrated with Schein organizational culture model to transform the organization underlying assumptions. The findings indicate that the formation of a guiding coalition and the achievement of short-term wins in administrative digitalization are key factors in reducing resistance and enhancing employee engagement. In conclusion, a structured change management approach is able to foster a more inclusive and adaptive organizational culture, which ultimately reduces employees’ turnover intention.